Femoro-distal bypass surgery at Groote Schuur Hospital: a 4-year retrospective study - Mwipatayi, Bibombe Patrice (Division of General Surgery, 2026)
The term "critical limb ischemia", while only defined in recent years by international consensus and objective arterial pressure measurements, has been recognized by surgeons since the dawn of reconstructive vascular surgery fifty years ago. Patients present with increasingly severe and intolerable ischemic rest pain involving a single toe or the entire forefoot. There is usually a preceding history of progressively worsening claudication. Ischemic rest pain is worse at night; it is not relieved by over-the-counter analgesics and eventually dominates the patient's existence. On presentation, these patients frequently exhibit tissue loss, gangrene, ischemic ulceration and forefoot infection. Critical limb ischemia represents the end stage of lower limb atherosclerotic disease, and multi-segmented arterial occlusion is the rule on angiogram.